2020
DOI: 10.1186/s12974-020-01797-2
|View full text |Cite
|
Sign up to set email alerts
|

Glioblastoma hijacks microglial gene expression to support tumor growth

Abstract: Background: Glioblastomas are the most common and lethal primary brain tumors. Microglia, the resident immune cells of the brain, survey their environment and respond to pathogens, toxins, and tumors. Glioblastoma cells communicate with microglia, in part by releasing extracellular vesicles (EVs). Despite the presence of large numbers of microglia in glioblastoma, the tumors continue to grow, and these neuroimmune cells appear incapable of keeping the tumor in check. To understand this process, we analyzed gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
72
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 87 publications
(73 citation statements)
references
References 72 publications
1
72
0
Order By: Relevance
“…Murine and human microglia can also respond in a similar way when confronted with pathological conditions. Recently, we showed that both the mouse and human microglial sensing potential is reduced in the context of glioma [ 3 ]. This suggests that microglia in the context of a tumor have a reduced capability to sense danger and can thus not fully execute their host-versus-tumor response.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Murine and human microglia can also respond in a similar way when confronted with pathological conditions. Recently, we showed that both the mouse and human microglial sensing potential is reduced in the context of glioma [ 3 ]. This suggests that microglia in the context of a tumor have a reduced capability to sense danger and can thus not fully execute their host-versus-tumor response.…”
Section: Discussionmentioning
confidence: 99%
“…Within a healthy brain, microglia have an important role in brain development and maintenance by clearing (cellular) debris. In pathological conditions, however, microglia can either limit disease progression or they can actually increase the burden of disease [ 2 , 3 , 4 ]. Recently, in addition to homeostatic microglia, a small subtype of microglia has been described based on their gene expression profile and role in disease progression, termed disease associated microglia (DAM) [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Glioma is a complex disease and the composition of the tumor environment, including glioma-infiltrating monocytes and macrophages, as well as microglia (Maas, Abels et al) has a substantial effect on tumor growth and response to therapy 36 . To elucidate the role of these cells in glioma we have aimed to decipher the molecular profile of these stromal cells.…”
Section: Discussionmentioning
confidence: 99%